A systematic overview, trends and global perspectives on blue carbon: A bibliometric study (2003–2021). (April 2023) - Zhong, Chongming; Li, Tangcheng; Bi, Ran; Sanganyado, Edmond; Huang, Jiahong; Jiang, Shuangcheng; Zhang, Zezhi; Du, Hong
Graphical abstract: Highlights: Landscape of blue carbon research from the perspective of bibliometrics. Blue carbon ecosystem was the main research area, but macroalgae deserve attention. Artificial intervention and methods are potential hotspots in the future research. Statistics, co-occurrence analysis and thematic evolution are main used methods. Abstract: Blue carbon sequestration is a nature-based solution to environmental problems caused by climate change and has a significant positive impact on the planet and human well-being. This paper bibliometrically and systematically analyzed 2, 613 studies found in the Web of Science Core Collection (WoSCC) from 2003 to 2021 to explore the hotspots and trends of blue carbon research using the Bibliometrix package in R studio and VOSviewer software. The results based on network co-occurrence analysis indicated that mangroves, seagrasses, and salt marshes were the major blue carbon ecosystems (BCEs), and mangrove carbon sinks were the most popular central research area. Furthermore, phytoplankton and microalgae have essential roles in the marine carbon cycle and bioenergy utilization, as revealed by the high proportion of published literature, while the carbon transport mechanisms of seagrass and macroalgae was understudied. Thematic evolution analysis revealed that remote sensing was the most commonly used technology as an emerging research field for ecological monitoring and ecological investigation in blue carbon research in recent years. In addition, increasing carbon sinks by artificial approaches, fishery carbon sinks, and carbon sequestration by macroalgae have been potential hotspots for blue carbon research development. The findings from this study shed light on the trends of blue carbon in the past eighteen years, current research points in the field, and areas that need more research investment going forward.